Stilistika Al-Qur’an: Memahami Bentuk-Bentuk Komunikasi Metafora dalam Surat Ali Imran - Hasaniyah, Nur; Faisol, Faisol; Murdiono, Murdiono (Arabi : Journal of Arabic Studies, 2023)
This research aims to delve into the stylistics of the Al-Qur’an, particularly the use of metaphorical communication (isti'arah) in Surat Ali Imran. This study uses a qualitative descriptive method to collect data from the Al-Qur’an, exegesis, and relevant literature. The research findings identify and analyze various forms of isti'arah employed in Surat Ali Imran, conveying metaphorical messages with linguistic uniqueness and brilliance. The analysis reveals that isti'arah serves as an effective tool for conveying religious concepts and enriches the reader's understanding through strong symbols and analogies. The research conclusion affirms that the presence of isti'arah in Surat Ali Imran enhances the Quranic language's beauty and adds depth to the comprehension of religious concepts. This metaphorical language style serves as a window that showcases the wisdom and grandeur of the Al-Qur’an, inviting readers to contemplate and understand divine messages more profoundly. Thus, this research provides valuable insights into the use of isti'arah in conveying metaphorical meanings in the Al-Qur’an, enriching Quranic readers' religious and linguistic understanding.